A novel flat-panel photobioreactor for simultaneous production of lutein and carbon sequestration by Chlorella sorokiniana TH01. (February 2022) - Van T. Do, Cam; Dinh, Cuc T.; Dang, Mai T.; Dang Tran, Thuan; Giang Le, Truong
Graphical abstract: Highlights: A novel flat-panel photobioreactor (FPP) was used for growing C. sorokiniana TH01. Algal biomass, lutein production and CO2 fixation in the single FPP was optimized. Optimal CO2, light and aeration were 5%, 150 µmol/m 2 /s and 1 L/min, respectively. Indoor serial FPPs reached lutein level of 9.14–9.86 mg/g and CO2 fixation of 100%. Outdoor serial FPPs obtained lutein level of 7.45–7.82 mg/g and CO2 fixation of 81%. Abstract: Carbon dioxide is the major cause of global warming. However, it is a carbon source for phototrophic production of chemicals from microalgae. In this work, a novel flat-panel photobioreactor (FPP) was used for maximization of biomass and lutein production and CO2 fixation by a lutein-rich C. sorokiniana TH01. CO2 concentration, light intensity and aeration rate were optimized as 5%, 150 µmol/m 2 /s and 1 L/min, respectively. The highest biomass productivity, lutein productivity and CO2 fixation efficiency were measured for indoor single and sequential FPPs were 284 – 469 mg/L/d, 2.57 – 4.57 mg/L/d, and 63 – 100%, respectively. In a climatic condition of 25.5 – 33 °C and 86 – 600 µmol/m 2 /s, C. sorokiniana TH01 achieved lutein productivity and CO2 fixation efficiency of 2.1 – 3.03 mg/L/d and 56 – 81%, respectively, while the comparable biomass productivity of 284 – 419 mg/L/d was maintained. This pioneered FPP system was efficiently demonstrated for production of algal lutein from CO2 .